2022
DOI: 10.1177/00202940211064471
|View full text |Cite
|
Sign up to set email alerts
|

Population size influence on the energy consumption of genetic programming

Abstract: Evolutionary Algorithms (EAs) are routinely applied to solve a large set of optimization problems. Traditionally, their performance in solving those problems is analyzed using the fitness quality and computing time, and the effect of evolutionary operators on both metrics is routinely used to compare different versions of EAs. Nevertheless, scientists face nowadays the challenge of considering the energy efficiency in addition to computational time, which requires studying the energy consumption of algorithms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…From the algorithmic perspective, a number of papers dealing with energy improvement have already been published [43], [44], [19], but these are the first exploratory papers on the ideas that may be applied to use energy consumption as a new optimization goal: the quality of the solutions is no longer the only relevant criterion, but it needs to be balanced with the energy consumption in mind, both during the training or optimization, and also when the solution itself is deployed massively for thousands or millions of users.…”
Section: E Software Optimization: Programming Languages Algorithms De...mentioning
confidence: 99%
See 1 more Smart Citation
“…From the algorithmic perspective, a number of papers dealing with energy improvement have already been published [43], [44], [19], but these are the first exploratory papers on the ideas that may be applied to use energy consumption as a new optimization goal: the quality of the solutions is no longer the only relevant criterion, but it needs to be balanced with the energy consumption in mind, both during the training or optimization, and also when the solution itself is deployed massively for thousands or millions of users.…”
Section: E Software Optimization: Programming Languages Algorithms De...mentioning
confidence: 99%
“…In any case, it is crucial to see how the algorithm behaves from the energy consumption point of view, so power consumption measures must be taken similarly to running times. As described in the literature review section, some interesting issues have been raised on the influence of some parameters on the energy consumption behavior of particular algorithms [44], so we foresee the same possibilities for future algorithms still to be conceived.…”
Section: B Energy Efficient Measures Of Interest At Different Levels ...mentioning
confidence: 99%
“…Previous studies have investigated the impact of this parameter on the performance of evolutionary algorithms [198,211,195]. In general, it can be concluded that the effect of the population on the performance of EC algorithms is complicated [65,201,222]. On the one hand, if the population size is small, the search capability of GP will be restricted and hence, the performance will be impacted negatively.…”
Section: The Effect Of Population Sizementioning
confidence: 99%